2003
DOI: 10.1080/02667360303234
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Emotional and Behavioural Difficulties

Abstract: This paper presents a critique of the educational model of emotional and behavioural difficulties in British education. In the wake of strong criticisms of the so-called medical model of maladjustment (pre-1980s), educational policies have defined the 'disturbing' pupil as having emotional and behavioural difficulties, and have more recently shifted towards reconstructing such difficulties as matters of discipline within school. The arguments from social science, semantics and ethics that were brought into pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…Further, the rhetoric of the child's needs masks a range of different needs: of the school to maintain order and to function successfully; of the parents to make sense of their child's behaviour or ability; and of professionals for a common language and rationale for the allocation of resources (Christian, 1997;Daniels & Cole, 2002;Molloy & Vasil, 2002). Decisions about the categorisation of individual pupils and about allocation of resources may depend more on the values, beliefs and interests of those making the judgements than on any attributes or qualities intrinsic to the child (Tomlinson, 1982;Sleeter, 1986;Armstrong & Galloway, 1996;Callias, 2001;Clough & Garner, 2003;Jones, 2003). There is room, therefore, for such decisions to be the subject of legitimate argument between professionals, parents and other interested parties.…”
Section: Munchausen Syndrome By Proxy and Children's Education: Profementioning
confidence: 97%
“…Further, the rhetoric of the child's needs masks a range of different needs: of the school to maintain order and to function successfully; of the parents to make sense of their child's behaviour or ability; and of professionals for a common language and rationale for the allocation of resources (Christian, 1997;Daniels & Cole, 2002;Molloy & Vasil, 2002). Decisions about the categorisation of individual pupils and about allocation of resources may depend more on the values, beliefs and interests of those making the judgements than on any attributes or qualities intrinsic to the child (Tomlinson, 1982;Sleeter, 1986;Armstrong & Galloway, 1996;Callias, 2001;Clough & Garner, 2003;Jones, 2003). There is room, therefore, for such decisions to be the subject of legitimate argument between professionals, parents and other interested parties.…”
Section: Munchausen Syndrome By Proxy and Children's Education: Profementioning
confidence: 97%
“…Por lo tanto, las representaciones acerca de la patología mental influyen en los comportamientos de quienes rodean al "enfermo" y asimismo en las políticas institucionales. Como crítica al tratamiento de niños con dificultades emocionales y comportamentales, generalmente etiquetados como "alumnos problemáticos" por el sistema educativo inglés, Jones (2003) puso de manifiesto las consecuencias del modelo médico en la concepción de dichos problemas.…”
Section: La Construcción Social Del Tdahunclassified
“…Esta medida implica des-integrar a los niños del ambiente educativo normal. De igual modo, al adjudicar al niño o a su problema la causa del desajuste, se da por hecho que la etiología es propiamente individual, razón por la cual no se consideran otros aspectos como dinámicas familiares o procesos educativos (Jones, 2003).…”
Section: La Construcción Social Del Tdahunclassified
“…In principle these measures represent a positive move in policy to catch those children who are at risk of requiring additional support during their educational career. However, as evidence from existing research would suggest (Jones, 2003; Levins, Bornholt & Lennon, 2005), where concerns over behavioural, emotional and social development (BESD) are raised, the emphasis is more often placed on the individual child or the parents in terms of causes and means of addressing the problem, despite the fact that this category is clearly identified as requiring additional support (NAW, 2002).…”
Section: Identification Of Needmentioning
confidence: 99%
“…Withdrawal, disengagement and problematic behaviour are common amongst children for whom a ‘hidden disability’ has not been correctly diagnosed. In recent years there have been a number of inquiries into the problematic nature of defining special educational needs, (Croll & Moses, 1985; Jones, 2003), with particular attention being given to such conditions. Further, it is suggested that the criteria for defining special educational needs are culturally and socially determined (Emerson, Hatton, Bromley & Caine, 1998; Galloway, Armstrong & Tomlinson, 1994), that is, a child's educational attainment is measured not only by the standards required by the framework of the education policy of the time, but by the child's ability to conform to academic, social, psychological and physical standards required in order to function effectively in the wider society after compulsory school age.…”
Section: Introductionmentioning
confidence: 99%